ACTOS DE HABLA COMPUESTOS Y ORACIONES COORDINADAS DE ENUNCIACIÓN - Vera Luján, Agustín; Blanco Rodríguez, Mercedes (Revista de Investigación Lingüística, 2006)
In the last years a number of researches have pointed out the need to take into consideration the description of a varied set of discourse processes in order to typify more in detail the whole group of syntactic relations operating at sentence level. Those researches have focussed on the subordination processes and have shown how important is the contrast between subordinate sentences at the énonciation and subordinate sentences at the énoncé. This analysis shows up to be highly profitable when describing the varied coordination patterns operating at sentence level which may be considered as the grammatical counterpart of a various set of compound speech acts.